Small Business Equity Returns: Empirical Evidence from the Business Credit Card Securitization Market - FLECKENSTEIN, MATTHIAS; LONGSTAFF, FRANCIS A. (Journal of Finance, 2023)
ABSTRACT We present a new approach for estimating small business equity returns. This approach applies the Merton (1974) credit model to the returns on entrepreneurial business credit card debt securitizations and solves for the implied equity returns for the small businesses owned by the cardholders. The estimated small business equity premium is 10.74%. The standard deviation of small business equity returns is 56.37%. We validate the methodology by applying it to investment‐grade corporate bonds and recovering a public equity premium of 6.17%.